2017
DOI: 10.1002/hep.29421
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M causes liver fibrosis by regulating cooperation between hepatic stellate cells and macrophages in mice

Abstract: Fibrosis is an important wound-healing process in injured tissues, but excessive fibrosis is often observed in patients with chronic inflammation. Although oncostatin M (OSM) has been reported to play crucial roles for recovery from acute liver injury by inducing tissue inhibitor of metalloproteinase 1 (Timp1) expression, the role of OSM in chronic liver injury (CLI) is yet to be elucidated. Here, we show that OSM exerts powerful fibrogenic activity by regulating macrophage activation during CLI. Genetic ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 49 publications
4
82
1
Order By: Relevance
“…In contrast to these studies, virally mediated OSM expression was shown to protect rats from hepatic fibrosis in the dimethylnitrosamine model of liver damage, an effect that likely depended on OSM‐induced hepatocyte regeneration. However, repeated delivery of an OSM‐expression vector to the livers of healthy mice by hydrodynamic tail vein injection resulted in pronounced liver fibrosis that featured high levels of Timp1 and Col1a1 expression . Furthermore, Osm −/− mice were protected from liver fibrosis in the thioacetamide model of chronic hepatitis .…”
Section: Potential Roles For Osm In Fibrosismentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to these studies, virally mediated OSM expression was shown to protect rats from hepatic fibrosis in the dimethylnitrosamine model of liver damage, an effect that likely depended on OSM‐induced hepatocyte regeneration. However, repeated delivery of an OSM‐expression vector to the livers of healthy mice by hydrodynamic tail vein injection resulted in pronounced liver fibrosis that featured high levels of Timp1 and Col1a1 expression . Furthermore, Osm −/− mice were protected from liver fibrosis in the thioacetamide model of chronic hepatitis .…”
Section: Potential Roles For Osm In Fibrosismentioning
confidence: 99%
“…However, repeated delivery of an OSM‐expression vector to the livers of healthy mice by hydrodynamic tail vein injection resulted in pronounced liver fibrosis that featured high levels of Timp1 and Col1a1 expression . Furthermore, Osm −/− mice were protected from liver fibrosis in the thioacetamide model of chronic hepatitis . Notably, OSM‐mediated liver fibrosis was shown to be driven by both hepatic stellate cells, which expressed TIMP‐1 in response to OSM, and liver macrophages, which responded to OSM by expressing the fibrogenic mediators TGF‐β1 and PDGF‐B .…”
Section: Potential Roles For Osm In Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the context, its functions include: activation of endothelium; induction of the acute phase response; induction of cellular proliferation and/or differentiation of cell types such as fibroblasts, epithelial cells and keratinocytes; modulation of erythropoiesis and megakaryopoiesis; inflammatory mediator release; and promotion of wound healing 4, 5, 6. OSM is implicated in a broad range of inflammatory and fibrotic diseases, including inflammatory bowel disease, liver fibrosis, idiopathic pulmonary fibrosis and systemic sclerosis (SSc) 4, 7, 8, 9, an autoimmune disease characterized by fibrosis of the skin and internal organs 10. As such, OSM is an important therapeutic target.…”
Section: Introductionmentioning
confidence: 99%